2017
DOI: 10.1111/vde.12473
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgE‐reactive proteins in hydrolysed dog foods

Abstract: Some commercial hydrolysed diets contain carbohydrate proteins. Some dogs have circulating IgE antibodies targeting these proteins. The clinical significance of these findings is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
1
16
1
Order By: Relevance
“…There are several reasons why undetected false‐negative results may have occurred. It has been reported that a minority of dogs with AFR can recognize ultrahydrolysed diets, and one study reported that some dogs develop IgE to carbohydrate proteins present in rice and cornstarch, such as maize‐derived granule‐bound starch synthase‐1 and rice‐derived glutelin type B1 . It also is possible that a longer trial period was needed for some nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons why undetected false‐negative results may have occurred. It has been reported that a minority of dogs with AFR can recognize ultrahydrolysed diets, and one study reported that some dogs develop IgE to carbohydrate proteins present in rice and cornstarch, such as maize‐derived granule‐bound starch synthase‐1 and rice‐derived glutelin type B1 . It also is possible that a longer trial period was needed for some nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…Another study excluded cross‐contamination with foreign proteins in over 2,500 batches of this diet, but reported the residual presence of granule‐bound starch synthase‐1 (GBSS1), an amylogenesis enzyme protein from corn starch ( Zea mays ) . In vitro reactivity with Cyno‐DIAL to GBSS1 in hydrolyzed diets has been reported . For the Royal Canin Anallergenic diet, reactivity was seen in that study in about 10% of the tested dogs, which is in line with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro reactivity with Cyno‐DIAL to GBSS1 in hydrolyzed diets has been reported . For the Royal Canin Anallergenic diet, reactivity was seen in that study in about 10% of the tested dogs, which is in line with the results of our study. However, in another study only 3% reactivity with the same serological assay and diet was reported .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations